Method of the rheostat for studying properties of fragments of theoretical sets - Yeshkeyev, A.R. (KU Publ., 2020)
In this article discusses the model-theoretical properties of fragments of theoretical sets and the rheostat method. These two concepts: theoretical set and rheostat are new. The study of this topic in the framework of the study of Jonsson theories, the Jonsson spectrum, classes of existentially closed models of such fragments is a new promising class of problems and their solution is closely related to many problems that once defined the classical problems of model theory. The purpose of this article is to determine the rheostat of the transition from complete theory to Jonsson theory, which will be consistent with the corresponding concepts for any and any -Jonsson theory. For this we define a theoretical set. On the basis of research by the author formulated a model-theoretical definition of the concept of a rheostat in the transition from complete theories to '(x)-theoretically convex Jonsson sets. Also was formulated an application of h-syntactic similarity to -Jonsson theories.
Теоретикалық жиындардың фрагменттерінің қасиеттерін зерттеу үшін реостат әдісі
Метод реостата для изучения свойств фрагментов теоретических множеств
Keywords: Jonsson theory; Jonsson spectrum; Jonsson set; theoretical set; fragment; rheostat